2017
DOI: 10.1007/s10880-017-9520-0
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Needs, Depressive Symptoms, and Suicide Ideation in a Sample of Portuguese Elderly Patients Recovering from Acute Medical Conditions

Abstract: The aim of the present study was to test whether perceived burdensomeness and thwarted belongingness are related to suicide ideation, when controlling for depressive symptoms. The sample consisted of elderly patients recovering from acute medical conditions who were recruited in a medical recovery clinic. Results demonstrated that depressive symptoms and thwarted belongingness related to the suicide ideation item of the Beck Depression Inventory-II, used as an indicator of suicide ideation. Depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
2
0
5
Order By: Relevance
“…Melihat kondisi lansia di Indonesia yang sebesar 26.20% menderita penyakit serta 51.8% mengalami keluhan kesehatan (Maylasari et al, 2019), perceived burdensomeness dapat disimpulkan rentan dialami lansia Indonesia. Kanzler, Bryan, Mcgeary, & Morrow (2012) perceived burdensomeness dan ideasi bunuh diri pada lansia, sedangkan penelitian dari Campos, Santos, Piteira, Abreu, & Tavares (2018) sebaliknya, tidak menemukan adanya korelasi yang signifikan antara dua variabel tersebut. Konstruk berikutnya dari teori interpersonal, yaitu thwarted belongingness, yang dideskripsikan sebagai perasaan terasingkan dari lingkungan sosial.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Melihat kondisi lansia di Indonesia yang sebesar 26.20% menderita penyakit serta 51.8% mengalami keluhan kesehatan (Maylasari et al, 2019), perceived burdensomeness dapat disimpulkan rentan dialami lansia Indonesia. Kanzler, Bryan, Mcgeary, & Morrow (2012) perceived burdensomeness dan ideasi bunuh diri pada lansia, sedangkan penelitian dari Campos, Santos, Piteira, Abreu, & Tavares (2018) sebaliknya, tidak menemukan adanya korelasi yang signifikan antara dua variabel tersebut. Konstruk berikutnya dari teori interpersonal, yaitu thwarted belongingness, yang dideskripsikan sebagai perasaan terasingkan dari lingkungan sosial.…”
Section: Pendahuluanunclassified
“…Penelitian dari McLaren, Gomez, Gill, & Chesler (2015) menyimpulkan bahwa thwarted belongingness memediasi ideasi bunuh diri pada kelompok dewasa akhir dengan status pernikahan. Campos, Santos, Piteira, Abreu, & Tavares (2018) juga mengatakan thwarted belongingness secara statistik memprediksi ideasi bunuh diri pada penelitiannya terhadap pasien lansia dengan riwayat penyakit medis akut. Menurut opini penulis sendiri, mudah bagi lansia merasa asing ketika ia tinggal bersama keluarga dan anak-anaknya di mana ia menjadi minoritas, sehingga memungkinkan terjadinya diskrepansi pola pikir antar generasi.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Other studies concentrate on the relationships between depressive symptoms and suicide. Depressive symptoms have been proven to be a promoting or risk factor for suicidal ideation, intent, and attempt (behaviour) (11)(12)(13)(14)(15)(16). Regarding the risk or hazard ratio, epidemiological research of over one hundred thousand samples revealed a high hazard ratio of suicide death in terms of mild (2.18), moderate (2.13), severe (3.33) and extremely heavy (3.67) depressive symptoms (17).…”
Section: Introductionmentioning
confidence: 99%
“…Исследование, проведенное R. Campos и соавт. [75,76], показало, что чувство брошенности и восприятие себя в качестве обузы стойко связаны с суицидальной идеацией и у лиц пожилого возраста.…”
unclassified